ETNOGRAFIC REALIA AND TRANSLATION FEATURES - Umarxonova, Guliruxsor (PT. Antis International Publisher, 2024)
The given article deals with study of ethnographic realia lexicon as well as interrelation of language and culture and analysis of which lies within translation, which is one of the most significant branches of modern linguistics. The aim of this research is to delve into the translation problems of ethnographic realia